THE EFFECT OF CLIMATE CHANGE ON RANGE LAND AND BIODIVERSITY: A REVIEW - Fereja, Getachew Bekele (International Journal of Research -GRANTHAALAYAH, 2017)
Rangelands are estimated to store up to 30 percent of the world’s soil carbon in addition to the substantial amount of above-ground carbon stored in trees, bushes, shrubs and grasses. Therefore this review was conducted to show the effect of climate change on range land and biodiversity. Climate change can have significant negative impacts on the natural environment including the loss of biodiversity and changes in ecosystems. The achievement of sustainable rangeland ecosystems remains a challenge for the world; rangeland degradation has not been arrested and the ecosystem services provided by the rangelands are not valued by the people in general or Governments in particular. The stresses imposed on rangeland by livestock production continue to rise, driven by rapid economic development and growing demand by urban people for more meat in diets. Many species around the world are now affected by the combined impacts of natural climate variability and anthropogenic climate change and their interactions with other human stressors such as the encroachment, fragmentation and destruction of natural habitats. Because of climate changes, species may no longer be adapted to the set of environmental conditions in a given region and could therefore fall outside its climatic niche. Climatic changes such as increased atmospheric concentration of CO2, changes in temperature, and changes in precipitation patterns have the potential to affect rangeland ecosystems. The direct effects of climate and climate change on rangeland ecosystem processes are fairly well described, have relatively short response times, and are somewhat easier to predict than the indirect effects. The evidence for human-induced climate change at the global level increases every day, yet it remains difficult to credibly predict how climate change will play out for any particular area.